The Influence of Expectancy Level and Personal Characteristics on Placebo Effects: Psychological Underpinnings - Zhou, Lili; Wei, Hua; Zhang, Huijuan; Li, Xiaoyun; Bo, Cunju; Wan, Li; Lu, Xuejing; Hu, Li (Frontiers in Psychiatry, 2019)
Placebo effects benefit a wide range of clinical practice, which can be profoundly influenced by expectancy level and personal characteristics. However, research on the issue of whether these factors independently or interdependently affect the placebo effects is still in its infancy. Here, we adopted a 3-day between-subject placebo analgesia paradigm (2-day conditioning and 1-day test) to investigate the influence of expectancy levels (i.e., No, Low, and High) and personal characteristics (i.e., gender, dispositional optimism, and anxiety state) on placebo effects in 120 healthy participants (60 females). Our results showed that the reduction of pain intensity in the test phase was influenced by the interaction between expectancy and gender, as mainly reflected by greater reductions of pain intensity in females at Low expectancy level than females at No/High expectancy levels, and greater reductions of pain intensity in males than in females at High expectancy level. Additionally, the reduction of pain unpleasantness was not only modulated by the interaction between expectancy and gender, but also by the interaction between expectancy and dispositional optimism, as well as the interaction between expectancy and anxiety state. Specifically, participants who were more optimistic in Low expectancy group, or those who were less anxious in High expectancy group showed greater reductions of pain unpleasantness. To sum up, we emphasized on regulating the expectancy level individually based on the assessment of personal characteristics to maximize placebo effects in clinical conditions.